Comparative Evaluation of Intrusion with Different Techniques - Mustafa Erkan; Sedat Mandıracı; Mehmet Demir Yiğit (Galenos Yayinevi, 2006)
The aim of this study was to compare the effectiveness of two fixed appliance techniques, which are commonly used for correction of a deep overbite. The study comprised of 38 patients (19 boys and 19 girls) in the treatment group with deep overbite (+4mm) and 20 patients (6 boys and 14 girls) in the control group (K) with Class II Div.1 malocclusion. Treatment group was divided into two subgroups as T1 and T2. In T1, 16 boys and 15 girls (total 31 patients) were treated with Rickets' utility arches, and in T2, 3 boys and 4 girls (total 7 patients) were treated with step down arches with horizontal loops. The study was carried out on 116 lateral cephalograms taken before and after the treatment in the treatment groups and the control period in the control group. In the cephalometric analyses, mandibular corpus axis inclination (FH / Xi-Pm), vertical displacement of Center of resistance of lower incisor (Cr-Xi Pm) and incisor inclination (Xi-Pm / B1-Br) were measured. It was found that the intrusion of lower incisor was 2.48 mm in T1 group and 2.50 mm in T2 group. With respect to increase of lower incisor inclination, it was 4.27° in the former and 2.92° in the latter. On the other hand, no significant changes in the mandibular corpus axis were observed in either of the groups. Statistically significant changes occurred in both treatment groups with treatment and these changes were again statistically significant when compared with those of the control group (P<0.01). No statistically significant changes were observed between the effects of two different treatment methods (P>0.05). Within the limitations of this study it is concluded that both treatment techniques were effective on incisor intrusion and can be used successfully with orthodontists' preference.